Exploring the plant volatile organic compounds in plant–insect interaction: A bibliometric analysis - Ashrith, V; Alagar, M; Suganthi, A; Shanmugam, P S; Amirtham, D; Murugan, M; Praneetha, S; Sheela, V; Senguttuvan, K; Aishwarya, P; et al. (Plant Science Today, 2025)
Plant volatile organic compounds (VOCs) are key components in plant-insect interactions, greatly influencing herbivory, pollination and tritrophic interactions. Despite the growing body of research exploring the chemical, ecological and applied aspects of VOCs, a systematic bibliometric synthesis to consolidate existing knowledge and identify emerging trends is still lacking. This review employs bibliometric and thematic analyses on 362 peer-reviewed publications to map the intellectual landscape of VOC research in plant–insect ecology. Data were retrieved through a structured search strategy and screened based on language and publication type. Notable trends include a sharp rise in VOC-related publications after 2013, with major contributions from journals such as Journal of Chemical Ecology and New Phytologist. Leading authors such as M. Dicke and T.C.J. Turlings have helped shape the field's direction, while collaborative networks reveal strong international partnerships, especially among the US, China, Germany and the UK as determined by citation frequency and network centrality metrics. Thematic mapping shows central focus areas on insect responses, plant defences and chemical signalling, with rising interdisciplinary interest in genomics, microbial ecology and climate impacts. Notably, gaps persist in macroevolutionary studies, belowground VOC signalling and field-based validations. This review highlights the evolving research frontiers and encourages deeper integration of VOC research with sustainable agriculture, molecular ecology and environmental resilience. These findings provide a valuable reference for guiding future studies and fostering innovation in plant-insect chemical ecology.